A Discrete Molecule and a 1D Coordination Polymer of Cadmium(II): Preparation, Structures, and Properties of [Cd(L1)2(NO3)2(CH3OH)] and [Cd(L2)(CH3COO)2]·(CH3OH)∞ (L1 = (4‐Py)–CH=N–C10H6–NH2; L2 = (3‐Py)–CH=N–C10H6–N=CH–(3‐Py)). (10th September 2019) - Ryu, Jihwan; Lee, Gang Min; Lee, Soon W.
Abstract : An asymmetric ligand, (4‐py)–CH=N–C10 H6 –NH2 (L 1 ), was prepared from 4‐pyridinecarboxaldehyde and 1, 5‐diaminonaphthalene. The ligand L 1 reacted with Cd(NO3 )2 ·4H2 O in methanol to give a discrete molecular complex, [Cd(L 1 )2 (NO3 )2 (CH3 OH)] (1 ). In addition, a 1D cadmium coordination polymer possessing a methanol molecule, [Cd(L 2 )(CH3 COO)2 ]·(CH3 OH)∞ (2 ), was prepared from a symmetric ligand (L 2 = (3‐py)–CH=N–C10 H6 –N=CH–(3‐py)) and Cd(OAc)2 ·2H2 O. Abstract : Packing diagram perpendicular to the [101] plane of compound 2.